Suicide Attempts, Neurocognitive Dysfunctions and Clinical Correlates in Middle-Aged and Elderly Chinese Schizophrenia Patients - Huang, Yuanyuan; Wu, Kai; Jiang, Rui; Zeng, Xiaoying; Zhou, Sumiao; Guo, Weijian; Feng, Yangdong; Zou, Caimei; Li, Hehua; Li, Ting; Ning, Yuping; Yang, Mingzhe; et al. (Frontiers in Psychiatry, 2021)
Background: Suicide is a common and complex symptom of schizophrenia that may be related to clinical variables and neurocognitive function. This study aimed to investigate the associated correlates of suicide attempts in Chinese middle-aged and elderly inpatients with schizophrenia, including demographic and clinical characteristics and cognitive level, which has not yet been reported. Methods: A total of 426 schizophrenia inpatients were recruited for this study. Clinical symptoms were evaluated using the Positive and Negative Syndrome Scale (PANSS). Neurocognitive function was measured by the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). Results: The prevalence of suicide attempts in middle-aged and elderly Chinese schizophrenia patients was 13.3%. Female patients had a higher suicide rate than male patients. Patients with suicide attempts had significantly higher PANSS-positive subscores, depressive subscores, and RBANS-story recall than non-attempter patients (all p < 0.05). Multiple logistic regression showed that gender, positive subscore, depressive subscore and RBANS-story recall (OR = 1.10–2.19, p < 0.05) were independently associated with suicide attempts in middle-aged and elderly schizophrenia patients. Conclusions: Our study showed that the rate of suicide attempts in Chinese middle-aged and elderly schizophrenia patients is high. Compared to non-attempters, there are less cognitive impairments, more clinical symptoms, and more female patients in the suicide attempters.